The resilience of emergency and critical care nurses: a qualitative systematic review and meta-synthesis - Liu, Shuyang; Zhang, Yu; Liu, Yue; Han, Peng; Zhuang, Yugang; Jiang, Jinxia (Frontiers in Psychology, 2023)
Background Due to the unique work environment, emergency and critical care departments nurses face high job pressure, often resulting in burnout and a high turnover rate. Public health emergencies such as the Corona Virus Disease 2019 pandemic tend to exacerbate these problems further. Therefore, improving the resilience of nurses is crucial to enhance their retention rates. Objective This systematic review and meta-synthesis of qualitative studies on the resilience of emergency and critical nurses were conducted to provide a reference for clinical managers to develop strategies for improving the resilience of nurses. Methods Following databases were searched for relevant studies: CINAHL Plus, Elsevier, Cochrane Library, Embase, Medline, OVID, Pubmed, Science Direct, LWW and Web of Science, China National Knowledge Network (CNKI), Wanfang Database (CECDB), VIP Database, and Sinomed. Google Scholar and Opengrey were used to search for gray literature. The literature search period was from the establishment of the database to April 2023. The systematic review of qualitative studies followed the Joanna Briggs Institute (JBI) approach, including critical appraisal using the JBI Checklist and synthesis through meta-synthesis. Confidence of evidence was assessed with JBI’s ConQual process. Results A total of 12 articles were identified, with 59 main results and 9 new integrated categories. Also, 3 themes, i.e., risk factors, protective factors, and personal growth, and 9 sub-themes, i.e., working pressure, negative emotion, an organizational issue, active learning, sense of occupational benefit, social support, self-cognition and regulation, learn to adapt, and self-actualization, were formed. Conclusion The resilience of emergency and critical care nurses depends on various factors. Managers should prioritize the mental health of nurses and implement measures to enhance their resilience through social support, team building, and psychological capital development. Additionally, management models can be updated based on domestic and international experience to improve nurses’ job involvement, optimize nursing quality, and promote the advancement of the nursing profession.